Frequency and Etiology of Secretory Otitis Media and its Morbidity in Children - Tallat Najeeb, Arshad Chohan,Musharaf Baig, Sayyed Ali Naqi (Journal of Rawalpindi Medical College, 2009)
Media with effusion(OME) among children in Rawalpindi region and to find out its aetiology and the associated hearing loss. Method: This descriptive study was conducted in Holy Family Hospital Rawalpindi over a period of one year (June, 7, 2007 to June, 7, 2008). Total of 563 children of 3-10 years of age presenting as out patients to ENT department during the research period were evaluated. Children with congenital anomalies of ears and impacted wax were excluded from the study. Thorough history was taken from parents of the child regarding hearing loss, tinnitus, discharge from ear, earache, itching in the ear, fever, rhinorhea, allergy, nasal obstruction, mouth breathing, recurrent sore throat, bottle feeding, language development and performance at school. Complete ENT examination was done. Hearing loss was assessed by pure tone audiometry (PTA) and OME was diagnosed with type B and C curve on tympanometry with hearing loss more than 25dB. Results: Out of 563 children, 306 were male and 257 were female. OME was common in 3-7 year age group with mean 5years. 65 children were still bottle-fed. Cleft lip and palate was found in 2, mouth breathing was seen in 29, simple rhinitis was present in 197, AURTI (acute upper respiratory tract infection) in 43 and hearing loss with delayed language development in 15 patients. On otoscopic examination, tympanic membrane was dull in 27 and retracted with decreased mobility in 20. OME was diagnosed in 39 children. 33 children showed type B curve with hearing loss of 30-40dB and 6 children showed type C curve with hearing loss of 25-30dB. Common symptoms in diagnosed cases were rhinitis in 21, mouth breathing (adenoids diagnosed on x-ray) in 13, cleft lip and palate in 2, hearing loss and delayed language development in 11 and AURTI in one child. All diagnosed cases had poor performance during their school activities. Conclusion: OME is a common disease in childhood and is closely related to various risk factors. It may result in serious morbidity in the form of delayed language development and poor performance at school due to hearing loss.